Electrodeposited Silver Nanowire Transparent Conducting Electrodes for Thin-Film Solar Cells - Lee, Sangyeob; Jang, Jiseong; Park, Taejun; Park, Young Min; Park, Joon Sik; Kim, Yoon Kee; Lee, Hyoung Keun; Jeon, Eun Chae; Lee, Doh Kwon; Ahn, Byungmin; Chung, Choong Heui (ACS Applied Materials and Interfaces, 2020)
Silver nanowire (AgNW) networks have demonstrated high optical and electrical properties, even better than those of indium tin oxide thin films, and are expected to be a next-generation transparent conducting electrode (TCE). Enhanced electrical and optical properties are achieved when the diameter of the AgNWs in the network is fairly small, that is, typically less than 30 nm. However, when AgNWs with such small diameters are used in the network, stability issues arise. One method to resolve the stability issues is to increase the diameter of the AgNWs, but the use of AgNWs with large diameters has the disadvantage of causing a rough surface morphology. In this work, we resolve all of the aforementioned issues with AgNW TCEs by the electrodeposition of Ag onto as-spin-coated thin AgNW TCEs. The electrodeposition of Ag offers many advantages, including the precise adjustment of the AgNW diameter and wire-to-wire welding to improve the junction conductance while minimizing the increase in protrusion height because of the overlap of AgNWs upon increasing the diameter. In addition, Ag electrodeposition on AgNW TCEs can provide higher conductance than that of as-spin-coated AgNW TCEs at the same transparency because of the reduced junction resistance, which generates a superior figure of merit. We applied the electrodeposited (ED) AgNW network to a Cu(In,Ga)Se2 thin-film solar cell and compared the device performance to a device with a standard sputtered transparent conducting oxide (TCO). The cell fabricated by the electrodeposition method showed nearly equal performance to that of a cell with the sputtered TCO. We expect that ED AgNW networks can be used as high-performance and robust TCEs for various optoelectronic applications.
Keywords: CIGS solar cells; Electrical and optical properties; Indium tin oxide thin films; Optical and electrical properties; Optoelectronic applications; Rayleigh instability; Silver nanowires; Transparent conducting electrodes; CIGS solar cell; electrodeposition; Rayleigh instability; silver nanowire; transparent electrode